Epidemiological profile of patients with anosmia after contamination by the SARS-CoV-2 virus in a city in west Paraná (Research, Society and Development, 2024)
Covid-19 emerged in China in 2019 and was declared a pandemic by the WHO in 2020. Among the main symptoms of this disease are fever, cough and dyspnea. Initially, anosmia and hyposmia were not attributed as characteristic symptoms of SARS-CoV-2 infection, but the correlation of this symptom with the disease was later proven. The study in question aims to define the epidemiological profile of patients over 18 years of age who had loss of smell after being affected by covid-19 in the city of Cascavel, Paraná, between the years 2020 and 2022. Sex, age group, evolution of the disease, existing comorbidities and symptoms associated with anosmia/hyposmia were analyzed. For the research, 64,371 cases were selected through the DataSus/TabNet and Notifica Covid database, with data collection carried out in the second half of 2023. The data was tabulated and analyzed in a Microsoft Excel spreadsheet. It was concluded that the loss of smell was more persistent in women, aged between 25 and 59 years and that this symptom was more common in cases reported in 2020 and 2021, with a reduction in 2022.